Target-site resistance to cyhalofop-butyl in bearded sprangletop (Diplachne fusca) from China. Issue 5 (24th June 2019) - Yuan, Shuzhong; Di, Yingjie; Chen, Yueyang; Chen, Yongrui; Cai, Jingxuan; Deng, Wei
Abstract: Bearded sprangletop [ Diplachne fusca (L.) P. Beauv. ex Roem. & Schult. ssp. fascicularis (Lam.) P. M. Peterson & N. Snow] is a noxious annual grass weed of paddy fields, distributed in coastal regions of the Jiangsu and Hebei provinces in China. Cyhalofop-butyl has been widely used to control grass weeds since 2006 in China. Overreliance on cyhalofop-butyl has led to the evolution of resistant weeds. In this study, the resistance level and cyhalofop-butyl resistance mechanisms were investigated in the putative resistant (JSHH) population. The dose–response experiments showed that the JSHH D . fusca population had evolved 8.9-fold resistance to cyhalofop-butyl. Acetyl-CoA carboxylase (ACCase) sequencing revealed a point mutation (GGC to GCC) at amino acid position 2096, resulting in a Gly-2096-Ala substitution in the resistant population. To our knowledge, this is the first case of cyhalofop-butyl resistance in D . fusca and the first report of a target-site mutation conferring resistance to ACCase-inhibiting herbicides in D . fusca . In addition, the resistant D . fusca population (JSHH) with the Gly-2096-Ala mutation was cross-resistant to the aryloxyphenoxypropionate herbicide metamifop, the cyclohexanedione herbicide sethoxydim, and the phenylpyrazolin herbicide pinoxaden.